Informal Reasoning Profile (IR) Students of SMA Negeri 1 Toroh, Grobongan District, Central Java Province - Fenny Roshayanti; Ipah Budi Minarti; Bella Woro Reca Liviviyanti (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2023)
Informal Reasoning (IR) is reasoning that is individual. Informal reasoning can be trained by providing questions based on socio-scientific issues. This study aims to determine the profile of Informal Reasoning (IR) students of class XI MIPA SMA Negeri 1 Toroh. The research subjects totaled 216 students. The sampling technique for this research is Proportionate Stratified Random Sampling. The method used is a survey via the Google Informal Reasoning (IR) test form in the form of multiple choice questions and descriptions, as well as supporting data in the form of teacher and student interview sheets and school observation sheets. The results showed that SMA Negeri 1 Toroh was categorized as 'good' with an average score of 73.8. The average percentage score for the 'good' category, namely 78.24%, was obtained because students' answers in responding to an issue could consider the risks and benefits as well as the emotional response to those related to the issue. The 'very good' category obtained a percentage of 15.74% because the students' answers in responding to social issues were already logical and used scientific language for various considerations of either sustainable losses or benefits. As for the category 'good enough' to get a percentage of 6.02%, it is known that students' answers respond to a social issue by considering a sense of concern. The results of mastery of each Informal Reasoning (IR) pattern are rational patterns with the highest acquisition of 46% then emotive patterns of 29%, while intuitive patterns with a percentage of 25%. Based on the research that has been carried out, it is concluded that the Informal Reasoning (IR) abilities of SMA Negeri 1 Toroh students are influenced by several factors including teacher competence, cognitive knowledge, regional demographics and infrastructure.